PELATIHAN TEKNIK PENGEMASAN UNTUK PRODUK UMKM BAGI GURU DI SMK YAPINUH - Winoto Hadi; Henita Rahmayanti; Dadang Suyadi S; Hendri Dunant H; Fanny Aulia N; Yogi Rahmadhani; Muhammad Iqbal; Renata Alvianita (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract Transportation is one of the key factors in the distribution of goods. The existence of transportation, distribution of products or goods can be easily packaged, collected in one place for short or long distances. Packaging itself is one way to protect or preserve food and non-food products. Packaging has an important role and function in supporting the distribution of products, especially those that are easily damaged. Yapinuh Vocational School is one of the vocational high schools in the Muara Gembong District, Bekasi Regency which plays a role in providing knowledge and skills for both students who are still in school, graduates and the community as a center of knowledge which in this case will provide proper packaging techniques as a distribution chain for processed service products. Yapinuh Vocational School together with the Faculty of Engineering, State University of Jakarta, in this case the Port Management and Maritime Logistics Study Program, collaborated to provide training in packaging techniques for processed service products. Abstrak Transportasi merupakan salah satu faktor kunci dalam hal pendistribusian barang. Adanya transportasi, pendistribusian produk atau barang dapat dengan mudah dikemas, dikumpulkan dalam satu tempat untuk jarak dekat maupun jarak jauh. Pengemasan itu sendiri merupakan salah satu cara untuk melindungi atau mengawetkan produk pangan maupun non-pangan. Pengemasan mempunyai peranan dan fungsi yang penting dalam menunjang distribusi produk terutama yang mudah mengalami kerusakan. SMK Yapinuh merupakan salah satu sekolah menengah kejuruan di wilayah Kecamatan Muara Gembong Kabupaten Bekasi yang berperan memberikan pengetahuan dan ketrampilan baik siswa yang masih bersekolah, lulusan maupun masyarakat sebagai sentra pengetahuan yang dalam hal ini akan memberikan Teknik pengemasan yang tepat sebagai rantai distribusi produk jasa olahan. SMK Yapinuh Bersama dengan Fakultas Teknik Universitas Negeri Jakarta dalam hal ini program studi STr Manajemen Pelabuhan dan Logistik Maritim berkerjasama memberikan pelatihan teknik pengemasan untuk produk jasa olahan.